The illustrated guide to the Bible - Porter, J. R. (Joshua Roy), 1921-2006. (New York : Oxford University Press, 2008)
Examines the Biblical narratives in their historical, social, archaeological, and mythological contexts and provides a section with a book-by-book summary of the Bible.
Originally published: New York : Oxford University Press, 1995.
Includes bibliographical references (pages 274-275) and index.
Keywords: Bible -- History of Biblical events; Bible -- Illustrations; Bible -- Introductions; Jews -- Civilization -- To 70 A.D.; Palestine -- Civilization; Pictures